Reestructuración técnico administrativa en la empresa Ferrelectricos Pinzón Caxx S.A.S. (2020)
To carry out the technical-administrative restructuring of the company Ferrel Eléctricos Pinzón CAXX located in Chía Cundinamarca, the development of four structured chapters was carried out to study and find the internal problems of the company, in order to be able to propose optimal solutions through engineering methodologies. industrial.